Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, Dan Ukuran Kap Terhadap Struktur Modal Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Lionel, Nicholas; Cynthia, Evelyn; Rajagukguk, Ronald Hasudungan; Siahaan, Septony Benyamin (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Indonesia Stock Exchange in 2020-2022. This research approach is based on a quantitative approach because this research has a clear and orderly flow. This type of research is a quantitative descriptive type of research. The nature of this research is descriptive explanatory. In this study, the population used was all mining companies listed on the Indonesia Stock Exchange from 2020 to 2022, totaling 28 companies. The results of this study indicate that Profitability has no partial effect on Capital Structure. Liquidity has a partial effect on Capital Structure. Company Size has no partial effect on Capital Structure. Profitability, Liquidity, and Company Size simultaneously affect Capital Structure.